2019
DOI: 10.1080/19768354.2019.1578262
|View full text |Cite
|
Sign up to set email alerts
|

Hydrangenol suppresses VEGF-stimulated angiogenesis by targeting p27KIP1-dependent G1-cell cycle arrest, VEGFR-2-mediated signaling, and MMP-2 expression

Abstract: We previously reported that hydrangenol has potent antitumor activity against human bladder cancer EJ cells. Here, we investigated the antiangiogenic activity of hydrangenol using in vitro and ex vivo models. Treatment with hydrangenol significantly inhibited the proliferation of vascular endothelial growth factor (VEGF)-induced HUVECs in a concentration-dependent manner (EC 50 = 10 μM). Flow cytometry analysis revealed that hydrangenol suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Hydrangenol (8-hydroxy-3-(4-hydroxyphenyl)-3,4-dihydroisochromen-1-one) is a natural dihydroisocoumarin mostly obtained from the Hydrangea species (Hydrangeaceae) leaves. Hydrangenol possesses antiinflammatory [250], antidiabetic [251], antioxidant [250,252], anticancer [253], and antiangiogenic activities [254]. It inhibited LPS-induced NO release and iNOS expression via suppression of NF-κB and consequently inhibiting NF-κB-DNA.…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…Hydrangenol (8-hydroxy-3-(4-hydroxyphenyl)-3,4-dihydroisochromen-1-one) is a natural dihydroisocoumarin mostly obtained from the Hydrangea species (Hydrangeaceae) leaves. Hydrangenol possesses antiinflammatory [250], antidiabetic [251], antioxidant [250,252], anticancer [253], and antiangiogenic activities [254]. It inhibited LPS-induced NO release and iNOS expression via suppression of NF-κB and consequently inhibiting NF-κB-DNA.…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…Hydrangenol (Figure 1), a natural dihydroisocoumarin, is mostly obtained from the leaves of hydrangea (Hydrangeaceae). Some researchers have reported that hydrangenol possesses antifungal [22], anti-allergic [23], antidiabetic [24], anti-inflammatory, [25] and anti-angiogenic activities [26]. In our previous study, hydrangenol isolated from the leaves of Hydrangea serrata (Thunb.)…”
Section: Introductionmentioning
confidence: 99%
“…14 Several studies have reported that both H. serrata extract and hydrangenol show anti-fungal, 17 anti-allergic, 18 anti-diabetic, 19 anti-inflammatory, 20 and anti-angiogenic activities. 21 We also previously reported the potent anti-aging activities of hyrangenol in UVB-induced Hs68 human fibroblasts and HR-1 hairless mice. 21,22 However, little is known about their potential anti-colitic effects.…”
Section: Introductionmentioning
confidence: 84%